Hieracium umbrosum subsp. abietinum (Asteraceae), a further example of amphi-Adriatic disjunction. (3rd September 2017) - Gottschlich, G.; Domina, G.; Di Gristina, E.
Abstract: So far considered as endemic to Greece, Hieracium umbrosum subsp. abietinum is reported as new for the Italian flora. Its presence has been noted on the Pollino National Park (S Italy). Morphological, ecological and taxonomical notes are given. This discovery increases the list of taxa showing an amphi-Adriatic distribution.